Psychosis and Cannabis: Could a Hasty Diagnosis and Treatment of Schizophrenia be Harmful? - Boulot, Zoé; F, Franck Gabayet; Besnard, Mathieu; Coulon, Nathalie (Archives of Clinical and Medical Case Reports, 2021)
We describe a young male patient who questions his diagnosis of schizophrenia made 10 years ago, and whose clinical presentation and history seem in favour of cannabisinduced psychotic episodes. This case questions the risk of a hasty diagnosis when it comes to concomitant psychosis and cannabis use. This presentation raises medical, therapeutical, and ethical questions. With cannabis use rising globally, cases like this are bound to multiply. There are no evident clinical distinctions between psychosis such as schizophrenia, and cannabis-induced psychosis described in literature, nor evidence-based guidelines on the care patients should benefit from. Further research is therefore needed.